Multinational People of Russian Federation (Russian Nation): Discursive Representation of a Political Subject - L. M. Golikov (Научный диалог, 2023)
On the basis of the ‘Strategy of State National Policy of the Russian Federation for the period until 2025’, this study examines the semantic and pragmatic features of representing the subject defined by the formula ‘multinational people of the Russian Federation (Russian nation)’, which serves as an actual instrument for expressing state ideology. The relevant attributes of the subject are reconstructed. It is established that the formula realizes the semantics of unity (integrity) at the legal, socio-cultural, and subjective levels. Unity is represented as the assumed state of the subject, acquired through the transformation of its normative, epistemic, and ethical orientations. Regular collocations representing situations causing the relevant attributes of the subject are identified and analyzed, with their implementation being the subject’s normative obligation. The axiological status of the formula is determined as a ‘normative judgment’, expressed through contrast with aberrations identified by lexemes that actualize the semantics of violating unity in political-legal texts. The ideological nature of the formula is demonstrated as a norm of ethical and epistemic nature, implying the subject’s internal non-utilitarian motivation based on its evaluation of unity (integrity) as an ideal and unconditionally true state.